What We Know about Human Traffickers in Vietnam - Le, Luong; Wyndham, Caitlin (Anti-Trafficking Review, 2022)
Myths and misconceptions about traffickers, the nature of trafficking, and how the crime varies in different jurisdictions pose challenges for prevention work, rehabilitating offenders, and achieving justice for victims. This article, based on an analysis of over 100 human trafficking court cases in Vietnam, outlines the reality of one particular trafficking crime: the trafficking of Vietnamese women and girls for sexual exploitation in China. We show that the majority of the prosecuted traffickers are similarly poor and vulnerable as their victims. Most are from ethnic minorities, with a poor educational background, and few income generation opportunities. Based on this evidence, we discuss some challenges associated with prosecution of these particular traffickers and suggest more effective approaches for human trafficking prevention.